2022
DOI: 10.3389/feart.2022.976732
|View full text |Cite
|
Sign up to set email alerts
|

Raindrop size distribution characteristics in summer of a nival glacial zone in eastern Tianshan, Central Asia

Abstract: Precipitation is a key component of the hydrological cycle, which is critical to understanding its formation and evolution. In this study, based on the observation data of the PWS100 located at the meteorological observation site at the terminal of Urumqi Glacier No. 1, eastern Tianshan Mountains, the statistical characteristics of the summer raindrop size distribution (DSD) were analyzed, and the DSD characteristics of five different rainfall rates(R) and two rainfall types (convective and stratiform) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Meanwhile, the low frequency of observation and lack of data limit researchers' in-depth understanding of precipitation patterns in mountain areas. A recent study showed that the DSD characteristics and microphysical parameters in the alpine region were quite different from those in other areas of the Tianshan Mountains, monsoon regions, and arid regions [42].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Meanwhile, the low frequency of observation and lack of data limit researchers' in-depth understanding of precipitation patterns in mountain areas. A recent study showed that the DSD characteristics and microphysical parameters in the alpine region were quite different from those in other areas of the Tianshan Mountains, monsoon regions, and arid regions [42].…”
Section: Introductionmentioning
confidence: 92%
“…The PWS100 and Geonor T-200B are installed in the meteorological observation field, A recent study showed a high correlation between the two instruments (0.8, n ≥ 731), which ensures that the observations from the PWS100 are valid [42]. The PWS100's built-in algorithm assumes that raindrops are deformed when they fall, and its internal code will exclude particles with unusual velocities [55].…”
Section: Quality Controlmentioning
confidence: 99%
See 3 more Smart Citations